2004
DOI: 10.1093/jjco/hyh089
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Conformal Radiation Therapy for Unresectable Hepatocellular Carcinoma Patients who had Failed with or were Unsuited for Transcatheter Arterial Chemoembolization

Abstract: 3DCRT induced a substantial tumor response rate of 61.4% with survival rates at 1, 2 and 3 years of 60.5%, 40.3% and 32.0%, respectively, and a median survival time of 15.2 months in patients with unresectable HCC who had either failed with or were unsuited for TACE. The complications are acceptable and can be managed with conservative treatment. Although we do not know whether there is a survival benefit through the use of this treatment, 3DCRT seems to be a practical method of salvage for this subset of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 31 publications
2
41
1
5
Order By: Relevance
“…The most common approaches include the use of 1 TACE procedure followed by RT, RT sandwiched between TACE procedures, 6 or repetitive TACE until optimal response or Ͼ 50% of normal liver is replaced by HCC followed by RT. 71 The interval between TACE and RT varies from 7 to 14 days, 10,62 3 to 4 weeks, 63,75 4 to 8 weeks, 39,61 and longer if RT is used as salvage therapy for tumor progression after TACE 10,70 (Table 4). A planned combined approach has some advantages over reserving RT as salvage therapy.…”
Section: Radiation and Tacementioning
confidence: 99%
See 2 more Smart Citations
“…The most common approaches include the use of 1 TACE procedure followed by RT, RT sandwiched between TACE procedures, 6 or repetitive TACE until optimal response or Ͼ 50% of normal liver is replaced by HCC followed by RT. 71 The interval between TACE and RT varies from 7 to 14 days, 10,62 3 to 4 weeks, 63,75 4 to 8 weeks, 39,61 and longer if RT is used as salvage therapy for tumor progression after TACE 10,70 (Table 4). A planned combined approach has some advantages over reserving RT as salvage therapy.…”
Section: Radiation and Tacementioning
confidence: 99%
“…The partial response rates range from 25% 71 to 78% 63 at 1 month after RT, with complete response rates as high as 13%. 6,39,63 The 2-year and 5-year survival rates range from 10.2% to 53.8% and from 9% to 19%, respectively. [61][62][63]66 The heterogeneity of disease, patients, and treatment make comparisons of reported series limited.…”
Section: Radiation and Tacementioning
confidence: 99%
See 1 more Smart Citation
“…When using X-ray or gamma-rays in SBRT, it may be referred to as X-knife or gamma-knife. The application of SBRT technology in the treatment of liver cancer has gradually been proven to be a safe and effective option (12)(13)(14)(15)(16) (18) reported a curative effect with the 'gamma-knife' in 56 patients with primary liver cancer, with an effective rate of 71.5% and a median survival time of 10.6 months; of note, the effective rate for tumor diameter <5 cm was 90%. SBRT for liver metastases over the last few years has exhibited satisfactory curative effects (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies have reported 2 year survival of 10% to 55% with combination of TACE and radiation. [21][22][23][24] A metananlyses from China, that included 5 randomized trials (in Chinese language) and 12 prospective studies included 1476 patients concluded that addition of RT to TACE can lead to 10-35% improvement in overall survival and higher odds of survival at 3 and 5 years. 25 Though the metanalyses included 5 randomized trials the methodological quality of trials was considered suboptimal and authors recommended the need for well conducted randomized studies investigating the role of additional RT.…”
Section: Introductionmentioning
confidence: 99%